Nano-mechanical properties of TaNbHfZr metallic glass films. (3rd August 2019) - Song, Baorui; Li, Yanhuai; Wang, Kehua; Cong, Zhonghao; Gao, Bo; Song, Zhongxiao; Chen, Jian
ABSTRACT: TaNbHfZr metallic glass films with thicknesses from 50 to 1000 nm were deposited on Si (100) wafers by magnetron sputtering. The surface topography and microstructure were confirmed by AFM, XRD and TEM. Nanoindentation was carried out to explore the effects of film thickness on the hardness and the deformation mechanisms. TaNbHfZr films thicker than 50 nm can effectively decrease the stress level on the Si substrate and suppress the indentation-introduced phase transition. Pile-ups took place for the thinner films (50 and 100 nm) due to the inactive thickness-dependent diffusion process, while sink-in for thicker films occur because of the high diffusion coefficient. Correction of H considering pile-ups and substrate effects was conducted to obtain the intrinsic surface hardness of ∼8 GPa. However, the corrected H for thin films with pile-up morphology are much lower as the localised plastic flow was strongly affected by the harder Si substrates and the retarded diffusion abilities of atoms.